2019
DOI: 10.1016/j.sleep.2019.11.1140
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of self-reported daytime sleepiness identifies 42 loci that suggest biological subtypes

Abstract: Excessive daytime sleepiness (EDS) affects 10-20% of the population and is associated with substantial functional deficits. Here, we identify 42 loci for self-reported daytime sleepiness in GWAS of 452,071 individuals from the UK Biobank, with enrichment for genes expressed in brain tissues and in neuronal transmission pathways. We confirm the aggregate effect of a genetic risk score of 42 SNPs on daytime sleepiness in independent Scandinavian cohorts and on other sleep disorders (restless legs syndrome, insom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 40 publications
(59 reference statements)
2
50
0
Order By: Relevance
“…Sleep lengths in twins have been similar as in other Finnish studies [ 27 ]. In addition, our twin cohort has taken part in multiple genome-wide association studies, with cohort specific effect size estimates that do not differ from the meta-analysis results [ 35 , 36 ]. The results are also valuable from an ontogeny point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep lengths in twins have been similar as in other Finnish studies [ 27 ]. In addition, our twin cohort has taken part in multiple genome-wide association studies, with cohort specific effect size estimates that do not differ from the meta-analysis results [ 35 , 36 ]. The results are also valuable from an ontogeny point of view.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have included the data (summary statistics) of the largest GWAS published to date. These studies had been approved by local ethics committees and had obtained the required informed consents (detailed in previously published papers) [36][37][38][39][40][41]43,44 . The overall study design is shown in Figure 1.…”
Section: Datasetsmentioning
confidence: 99%
“…Number of genes p-value considered* ADHD 42 NA NA Sleep duration 36 48 2.78x10 -6 Long sleep duration 40 14 2.78x10 -6 Short sleep duration 40 32 2.78x10 -6 Daytime sleepiness 38 38 2.78x10 -6 Snoring 36 33 2.78x10 -6 Insomnia 36 44 2.78x10 -6 Insomnia 37 75 2.78x10 -6 Daytime dozing 36 2 2.78x10 -6 Daytime napping 36 8 2.78x10 -6 *p-value of Bonferroni correction test; NA = not-applicable.…”
Section: Phenotypesmentioning
confidence: 99%
“…Are these experimental findings in model systems relevant to humans? Our analysis of several self-reported sleep traits ( N = 450,000) in humans of European ancestry from the U.K. Biobank ( 4 8 , 24 ) identified genome-wide significant associations of several sleep traits with common variants in the KSR2 and ERBB4 genomic loci. KSR2 is a scaffolding protein that enables interaction of the EGFR signaling components RAF, MEK, and ERK, and thus is crucial for EGFR signaling ( 46 ).…”
Section: Discussionmentioning
confidence: 94%
“…6, A and C to E, and table S1). In addition, pathway analysis for EDS revealed associations at EGFR signaling pathways enriched in the sleep propensity subtype of daytime sleepiness ( 4 ). Together, these results suggest that the identified genetic variants in the ERBB4 and KSR2 loci associate with measures of increased sleep.…”
Section: Resultsmentioning
confidence: 99%